PENDAMPINGAN MANAJEMEN KEUANGAN PEDAGANG KAKI LIMA PASAR MANONDA BINAAN BAZNAS PROVINSI SULAWESI TENGAH - Muliati Muliati; Arung Gihna Mayapada; Abdul Pattawe (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Street vendors as part of micro, small, and medium enterprises are the main contributors to the Indonesian economy in general and Palu City in particular. Even so, the development of street vendors’ businesses are not significant and do not even last long. This is due to the lack of awareness and knowledge regarding effective and efficient business financial management. The community service team in collaboration with the National Amil Zakat Agency (Baznas) of Central Sulawesi Province held financial management assistance to street vendors at Manonda Traditional Market who received capital assistance from Baznas of Central Sulawesi Province in 2021. The method of implementing the service through brainstorming and supervision was chosen because street vendors would be given awareness and knowledge of financial management and assisted in its implementation. Mentoring would be given to 20 street vendros, each of whom received IDR 500,000. Brainstroming was done to provide awareness and direction to street vendors regarding good financial management. Supervision was carried out in order to ensure the sustainability of the financial management implementation that has been taught. All service activities were carried out well and enthusiastically received by Baznas of Central Sulawesi Province as partner and street vendors at Manonda Market as beneficiaries.